Effect of repeated head impacts on amount of cervical vertebral translation among collegiate American football players - Saaya Umeoka; Satoru Nishida; Takashi Fukuda (Japanese Society of Physical Fitness and Sports Medicine, 2023)
American football is associated with a high risk of cervical injuries. In order to prevent these injuries, head acceleration during head impacts is currently being studied, but no studies have examined the effects on the neck. We aimed to examine the effects of head impact kinematics (the number of head impacts, maximum head linear acceleration [LA], and maximum head angular acceleration [AA]) on cervical vertebral translation (VT) in collegiate American football players over a one-year period. Twenty-two players (5 linemen and 17 skill players) who belonged to T university in the Kantoh Collegiate American Football Association Division 2. We examined the relationship between the total number of head impact kinematics over a 1-year period and the amount of cervical vertebral translation as measured by a mouth guard with a 6-axis accelerometer. The total number of head impacts of subjects was 12,368. For skill players, the 4th cervical vertebral movement distance was significantly correlated with the maximum AA (r = 0.49, P = 0.04) and also with the maximum LA (r = 0.48, P = 0.05). In Japanese collegiate American football players, it was suggested that the repeated head impacts with large maximum LA and AA generated in the head affected the amount of the 4th cervical vertebral translation. In particular, skill players were affected, so they need to develop safer tackle skills even when tackling at high speed. This may result in a decrease in acceleration during head impact, leading to a decrease in the load on the cervical spine.